Evolution of Tafsir Approaches in Islamic Studies - Bahrudin, Andre; Muchtar, Aflatun; Romli SA, Romli SA; Hidayatullah, Hidayatullah; Afryansyah, Afryansyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This study explores the evolution of interpretive approaches in the study of the Qur'an, emphasizing their historical progression and contemporary relevance. Using qualitative library research, primary data were sourced from classical and contemporary exegesis texts, while secondary data included scholarly works and related studies. Analytical methods involved content and interpretive analysis. The findings reveal a dynamic development of Qur'anic exegesis, beginning with the Prophet Muhammad's oral interpretations, evolving through the companions' systematic methods, and culminating in modern interdisciplinary approaches. Contemporary methods, such as hermeneutics, thematic analysis, and maqasid al-shari'ah-based exegesis, highlight a shift toward contextual understanding and integration of social sciences and sciences in interpretation. These methodologies address pressing modern issues, including gender equality, environmental sustainability, and digital literacy, aligning Qur'anic principles with current societal needs. The study underscores the critical role of modern exegetical approaches in bridging traditional Islamic scholarship with contemporary challenges, ensuring the Qur'an's continued relevance in guiding ethical, social, and scientific endeavors.